'Abandonment' and the acquisition of property rights in separated human biomaterials. (September 2016) - Maddox, Neil
This article offers a critique of the concept of 'abandonment' when utilized in relation to separated human biomaterials. In the absence of the recognition of even limited property rights in the human source of such materials, the author contends that utilizing abandonment is meaningless and misleading. Absurd consequences need not result from recognition of such rights and indeed most cases of purported abandonment of human tissue are more akin to voluntary transfers. Describing such transfers in terms of abandonment obscures questions as to the agency and the scope of the fiduciary duties of medical professionals and researchers. Income rights in such materials are more appropriately determined as normative questions as to who should benefit from windfall wealth in human biomaterials, not by reference to abandonment. An alternative framework that recognized that the source of human tissue had limited property rights in it would solve many of the conceptual difficulties outlined.